A high-performance composite material for building and preparation method thereof
By using PA10T matrix resin, PPO, flat glass fiber and aramid fiber in building formwork materials, high-performance composite materials are prepared, which solves the problems of insufficient stiffness and toughness and high water absorption of existing materials, and achieves the flame retardant, excellent mechanical properties and improved surface performance of the materials.
Patent Information
- Application Number
- CN202411147743.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-08-21
AI Technical Summary
The existing building formwork materials have problems such as insufficient stiffness and toughness, large water absorption and thermal expansion coefficient, and rough surface during construction, which affects the quality of the project and construction safety.
PA10T is used as the matrix resin, combined with PPO, flat glass fiber and aramid fiber, and added flame retardant, coupling agent, antioxidant and flow modifier to prepare high-performance building composite materials through high mixing machines and extrusion mechanisms.
The composite material has achieved flame retardant, excellent mechanical properties, low water absorption, and improved surface performance through uniform fiber dispersion, enhancing the dimensional stability and construction applicability of the material.
Smart Images

Figure FCE9DWME5HGG08NHH4ZY8ETGDF19FGFD2DZVS2VM 
Figure HJPIEO1ZWDLB4XA1ECPOIJMJAVBE7PU70SDG9FBG
Abstract
Description
Technical Field
[0001] The invention belongs to the field of modified polymer materials, and in particular relates to a high-performance composite material for construction and a preparation method thereof. Background Art
[0002] Since the 1990s, my country's building structure system has undergone great changes. Cast-in-place reinforced concrete structures account for an increasing proportion of civil engineering, and high-rise and super-high-rise reinforced concrete buildings have emerged in large numbers. Cast-in-place concrete structure construction requires the use of building formwork, which is mainly composed of three parts: panel, support structure and connectors. Among them, the panel is a load-bearing plate that directly contacts the newly poured concrete; the support structure is a temporary structure that supports the panel, concrete and construction load; the connector is an accessory that can connect the panel and the support structure into a whole.
[0003] Although the building formwork is a temporary support structure, it must be made according to the design requirements to ensure that the concrete structure and components are formed according to the expected position, shape and geometric dimensions, while bearing their own weight and external loads. During construction, it is necessary to ensure the quality of the concrete project, the construction progress and the safety of operation, so there are high requirements for the panels that contact the concrete. The building formwork panel should have sufficient strength to ensure the bearing capacity of the formwork system; it should have sufficient elastic modulus to ensure the overall rigidity of the formwork system. In addition, the surface of the formwork panel should be flat and smooth, and lightweight and durable materials should be selected as much as possible, so that it can be recycled many times without damage.
[0004] At present, the mainstream building formworks on the market are divided into metal formworks and plastic formworks. Metal formworks have good dimensional stability and a wide range of applications. However, in use, metal formworks have exposed many problems, such as many joints, resulting in poor surface flatness of the concrete; heavy weight, inconvenient transportation and loading and unloading. With the proposal of the policy of "replacing steel with plastics", the plastic industry has developed rapidly, and people have begun to use it to replace traditional building decoration materials and building formwork materials.
[0005] Nylon formwork has good physical properties such as good water resistance, no decay, no rust, no affinity with cement, and no adhesion. It ensures the flatness of the concrete surface during construction and is easy to carry and install. However, the rigidity and toughness of existing nylon formwork are insufficient, and a unique support system or multi-point support is required during construction; in addition, nylon formwork has large water absorption and thermal expansion coefficient, and will produce certain deformation when the temperature difference changes and the water content is large, which is not conducive to the control of project quality. For this reason, glass fiber is often added for reinforcement during the manufacturing process, but the addition of fiber can easily cause surface roughness and affect the performance of the building. Summary of the invention
[0006] In order to solve the above technical problems, the present invention provides a high-performance building composite material and a preparation method thereof. The building composite material not only has excellent flame retardancy and mechanical properties, and low water absorption, but also realizes uniform dispersion of fibers in a nylon matrix, thereby improving the surface properties of the product.
[0007] In order to achieve the above object, the present invention adopts the following technical solution:
[0008] A high-performance composite material for construction, comprising the following components in parts by weight:
[0009] PA10T 80-90 parts, PPO 15-25 parts, flat glass fiber 20-30 parts, aramid fiber 5-10 parts, flame retardant 4-10 parts, coupling agent 1-5 parts, antioxidant 1-3 parts, flow modifier 1-3 parts.
[0010] PA10T is a new type of high temperature resistant material with high melting point and excellent high temperature resistance. At the same time, its diamine flexible long chain length is moderate, which not only takes into account the advantages of high toughness of PA12T, but also has the characteristics of high rigidity of PA6T and PA9T. However, as a long carbon chain semi-aromatic nylon, its rigidity still cannot meet the use requirements of building materials. In order to improve the mechanical properties of PA10T, the present invention adds a certain amount of PPO. The polyphenylene ether molecular chain contains a large number of benzene rings, has good hardness and rigidity, high tensile strength and bending strength, good creep resistance, and can improve the dimensional stability of PA10T; and polyphenylene ether does not contain hydrolyzed functional groups, and has very low water absorption, which greatly reduces the water absorption of nylon composite materials and prevents the composite materials from absorbing water and deforming in a humid environment. Further, the amount of polyphenylene ether used is 20-25 parts, which is conducive to the uniform dispersion of fiber fillers and improves the density of composite materials within this range; it can also give full play to the performance of polyphenylene ether itself and improve the mechanical properties of composite materials.
[0011] The addition of flat glass fiber and aramid fiber can greatly improve the mechanical properties and creep resistance of PA10T. Compared with ordinary glass fiber, the melt flow performance of flat glass fiber composite material is better, especially in terms of warping deformation, the warping deformation of flat glass fiber is only 1 / 4 of that of ordinary glass fiber composite material. And the cross-section of flat glass fiber is a special-shaped structure, which is more conducive to forming an intertwined network structure with aramid fiber. As an organic polyamide fiber, aramid fiber has excellent compatibility with PA10T, which can improve the dispersion performance of flat glass fiber in PA10T matrix and prevent the occurrence of floating fiber phenomenon. The addition of aramid fiber not only plays a role in strengthening and toughening, but more importantly, it acts as a dispersing aid for flat glass fiber to improve the surface properties of the composite material. If the amount of aramid fiber is too small, its strengthening effect is limited; however, if the amount is too large, it is easy to cause uneven fiber dispersion and cause floating fiber phenomenon.
[0012] The PA10T melt index is 10-20 g / 10 min.
[0013] The ratio of the major diameter to the minor diameter of the flat glass fiber is 2-10, and the length thereof is 1-10 mm.
[0014] The aramid fiber is Kevlar fiber, and its length is 1-10 mm.
[0015] The flame retardant comprises a main flame retardant and a synergistic flame retardant; the main flame retardant is an alkyl phosphinate; the synergistic flame retardant is one or more of zinc borate, zinc oxide, aluminum oxide or magnesium hydroxide.
[0016] The coupling agent is one or more of KH550, KH560 and KH570.
[0017] The antioxidant is one or more of hindered phenol antioxidants, hindered amine antioxidants, phosphate antioxidants, and phosphite antioxidants.
[0018] The flow modifier is one or more of silicone powder, polytetrafluoroethylene, amide wax, stearic acid amide, calcium stearate, and zinc stearate.
[0019] The present invention also provides a method for preparing a high-performance building composite material, comprising the following steps:
[0020] (1) Place PA10T, PPO, flame retardant, coupling agent, antioxidant and flow modifier in a high-speed mixer and mix evenly;
[0021] (2) The mixed material prepared in step (1) is added to an extruder through a main feed port, and flat glass fibers and aramid fibers are added to the extruder through a side feed port. The mixed material is melt-extruded, cooled, dried, and pelletized through the extruder to obtain a high-performance composite material for construction.
[0022] The heating temperature of the extruder is 310-330° C., and the screw speed is 500-700 r / min.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The present invention uses PA10T as a matrix resin, which not only takes into account the advantages of high toughness of PA12T, but also has the characteristics of high rigidity of PA6T and PA9T. The polyphenylene ether molecular chain contains a large number of benzene rings, has good hardness and rigidity, has high tensile strength and flexural strength, and has good creep resistance. It can improve the dimensional stability of PA10T and reduce the water absorption of nylon composite materials. The addition of flat glass fiber and aramid fiber can greatly improve the mechanical properties and creep resistance of PA10T. The addition of aramid fiber not only plays a role in strengthening and toughening, but more importantly, it acts as a dispersing aid for flat glass fiber to improve the surface properties of the composite material. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] Unless otherwise specified, the raw materials used in the examples and comparative examples are the same. Among them, the PA10T melt index is 15g / 10min. The long diameter of the flat glass fiber cross section is 28μm, the short diameter is 7μm, and the fiber length is 3mm; the diameter of the ordinary round cross-section glass fiber is 10μm and the fiber length is 3mm. The aramid fiber is Kevlar fiber, and its length is 7mm. The coupling agent is KH560. The antioxidant is bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphate.
[0027] Example 1
[0028] A high-performance composite material for construction, comprising the following components in parts by weight:
[0029] 80 parts of PA10T, 20 parts of PPO, 20 parts of flat glass fiber, 5 parts of aramid fiber, 4 parts of flame retardant, 1 part of coupling agent, 1 part of antioxidant, and 1 part of flow modifier. The flame retardant includes a main flame retardant and a synergistic flame retardant; the main flame retardant is aluminum diethylphosphinate; the synergistic flame retardant is zinc borate; the mass ratio of the main flame retardant to the synergistic flame retardant is 3:1. The flow modifier is polytetrafluoroethylene.
[0030] Example 2
[0031] A high-performance composite material for construction, comprising the following components in parts by weight:
[0032] 90 parts of PA10T, 25 parts of PPO, 30 parts of flat glass fiber, 10 parts of aramid fiber, 10 parts of flame retardant, 5 parts of coupling agent, 3 parts of antioxidant, and 3 parts of flow modifier. The flame retardant includes a main flame retardant and a synergistic flame retardant; the main flame retardant is aluminum diethylphosphinate; the synergistic flame retardant is zinc oxide; the mass ratio of the main flame retardant to the synergistic flame retardant is 5:1. The flow modifier is calcium stearate.
[0033] Example 3
[0034] A high-performance composite material for construction, comprising the following components in parts by weight:
[0035] 80 parts of PA10T, 25 parts of PPO, 30 parts of flat glass fiber, 5 parts of aramid fiber, 10 parts of flame retardant, 5 parts of coupling agent, 1 part of antioxidant, and 1 part of flow modifier. The flame retardant includes a main flame retardant and a synergistic flame retardant; the main flame retardant is aluminum diethylphosphinate; the synergistic flame retardant is aluminum oxide; the mass ratio of the main flame retardant to the synergistic flame retardant is 4:1. The flow modifier is zinc stearate.
[0036] Example 4
[0037] A high-performance composite material for construction, comprising the following components in parts by weight:
[0038] 90 parts of PA10T, 20 parts of PPO, 20 parts of flat glass fiber, 10 parts of aramid fiber, 5 parts of flame retardant, 4 parts of coupling agent, 2 parts of antioxidant, 1 part of flow modifier. The flame retardant includes a main flame retardant and a synergistic flame retardant; the main flame retardant is aluminum diethylphosphinate; the synergistic flame retardant is zinc borate; the mass ratio of the main flame retardant to the synergistic flame retardant is 4:1. The flow modifier is polytetrafluoroethylene.
[0039] Example 5
[0040] A high-performance composite material for construction, comprising the following components in parts by weight:
[0041] 83 parts of PA10T, 22 parts of PPO, 22 parts of flat glass fiber, 6 parts of aramid fiber, 5 parts of flame retardant, 2 parts of coupling agent, 2 parts of antioxidant, and 2 parts of flow modifier. The flame retardant includes a main flame retardant and a synergistic flame retardant; the main flame retardant is aluminum diethylphosphinate; the synergistic flame retardant is zinc oxide; the mass ratio of the main flame retardant to the synergistic flame retardant is 6:1. The flow modifier is calcium stearate.
[0042] Example 6
[0043] A high-performance composite material for construction, comprising the following components in parts by weight:
[0044] 88 parts of PA10T, 24 parts of PPO, 27 parts of flat glass fiber, 8 parts of aramid fiber, 8 parts of flame retardant, 3 parts of coupling agent, 3 parts of antioxidant, and 3 parts of flow modifier. The flame retardant includes a main flame retardant and a synergistic flame retardant; the main flame retardant is aluminum diethylphosphinate; the synergistic flame retardant is aluminum oxide; the mass ratio of the main flame retardant to the synergistic flame retardant is 4:1. The flow modifier is zinc stearate.
[0045] Example 7
[0046] A high-performance composite material for construction, comprising the following components in parts by weight:
[0047] 85 parts of PA10T, 23 parts of PPO, 25 parts of flat glass fiber, 8 parts of aramid fiber, 6 parts of flame retardant, 3 parts of coupling agent, 2 parts of antioxidant, and 2 parts of flow modifier. The flame retardant includes a main flame retardant and a synergistic flame retardant; the main flame retardant is aluminum diethylphosphinate; the synergistic flame retardant is zinc borate; the mass ratio of the main flame retardant to the synergistic flame retardant is 4:1. The flow modifier is zinc stearate.
[0048] Example 8
[0049] A high-performance composite material for construction, comprising the following components in parts by weight:
[0050] 85 parts of PA10T, 15 parts of PPO, 25 parts of flat glass fiber, 8 parts of aramid fiber, 6 parts of flame retardant, 3 parts of coupling agent, 2 parts of antioxidant, and 2 parts of flow modifier. The flame retardant includes a main flame retardant and a synergistic flame retardant; the main flame retardant is aluminum diethylphosphinate; the synergistic flame retardant is zinc borate; the mass ratio of the main flame retardant to the synergistic flame retardant is 4:1. The flow modifier is zinc stearate.
[0051] Comparative Example 1
[0052] A high-performance composite material for construction, comprising the following components in parts by weight:
[0053] PA10T 85 parts, PPO 23 parts, flat glass fiber 0 parts, aramid fiber 33 parts, flame retardant 6 parts, coupling agent 3 parts, antioxidant 2 parts, flow modifier 2 parts. The flame retardant includes a main flame retardant and a synergistic flame retardant; the main flame retardant is aluminum diethylphosphinate; the synergistic flame retardant is zinc borate; the mass ratio of the main flame retardant to the synergistic flame retardant is 4:1. The flow modifier is zinc stearate.
[0054] Comparative Example 2
[0055] A high-performance composite material for construction, comprising the following components in parts by weight:
[0056] 85 parts of PA10T, 23 parts of PPO, 33 parts of flat glass fiber, 0 parts of aramid fiber, 6 parts of flame retardant, 3 parts of coupling agent, 2 parts of antioxidant, and 2 parts of flow modifier. The flame retardant includes a main flame retardant and a synergistic flame retardant; the main flame retardant is aluminum diethylphosphinate; the synergistic flame retardant is zinc borate; the mass ratio of the main flame retardant to the synergistic flame retardant is 4:1. The flow modifier is zinc stearate.
[0057] Comparative Example 3
[0058] A high-performance composite material for construction, comprising the following components in parts by weight:
[0059] 85 parts of PA10T, 23 parts of PPO, 25 parts of flat glass fiber, 3 parts of aramid fiber, 6 parts of flame retardant, 3 parts of coupling agent, 2 parts of antioxidant, and 2 parts of flow modifier. The flame retardant includes a main flame retardant and a synergistic flame retardant; the main flame retardant is aluminum diethylphosphinate; the synergistic flame retardant is zinc borate; the mass ratio of the main flame retardant to the synergistic flame retardant is 4:1. The flow modifier is zinc stearate.
[0060] Comparative Example 4
[0061] A high-performance composite material for construction, comprising the following components in parts by weight:
[0062] 85 parts of PA10T, 23 parts of PPO, 25 parts of flat glass fiber, 15 parts of aramid fiber, 6 parts of flame retardant, 3 parts of coupling agent, 2 parts of antioxidant, and 2 parts of flow modifier. The flame retardant includes a main flame retardant and a synergistic flame retardant; the main flame retardant is aluminum diethylphosphinate; the synergistic flame retardant is zinc borate; the mass ratio of the main flame retardant to the synergistic flame retardant is 4:1. The flow modifier is zinc stearate.
[0063] Comparative Example 5
[0064] A high-performance composite material for construction, comprising the following components in parts by weight:
[0065] 85 parts of PA10T, 23 parts of PPO, 25 parts of ordinary round cross-section glass fiber, 8 parts of aramid fiber, 6 parts of flame retardant, 3 parts of coupling agent, 2 parts of antioxidant, and 2 parts of flow modifier. The flame retardant includes a main flame retardant and a synergistic flame retardant; the main flame retardant is aluminum diethylphosphinate; the synergistic flame retardant is zinc borate; the mass ratio of the main flame retardant to the synergistic flame retardant is 4:1. The flow modifier is zinc stearate.
[0066] Comparative Example 6
[0067] A high-performance composite material for construction, comprising the following components in parts by weight:
[0068] 85 parts of PA10T, 30 parts of PPO, 25 parts of flat glass fiber, 8 parts of aramid fiber, 6 parts of flame retardant, 3 parts of coupling agent, 2 parts of antioxidant, and 2 parts of flow modifier. The flame retardant includes a main flame retardant and a synergistic flame retardant; the main flame retardant is aluminum diethylphosphinate; the synergistic flame retardant is zinc borate; the mass ratio of the main flame retardant to the synergistic flame retardant is 4:1. The flow modifier is zinc stearate.
[0069] The preparation method of the embodiment and comparative example comprises the following steps:
[0070] (1) Place PA10T, PPO, flame retardant, coupling agent, antioxidant and flow modifier in a high-speed mixer and mix evenly;
[0071] (2) The mixed material prepared in step (1) is added to the extruder through the main feed port, and the flat glass fiber and aramid fiber are added to the extruder through the side feed port. The mixture is melt-extruded, cooled, dried, and pelletized by the extruder to obtain a high-performance composite material for construction. The heating temperature of the extruder is 320° C. and the screw speed is 600 r / min.
[0072] The high-performance building composite materials of Examples 1-8 and Comparative Examples 1-6 were prepared into standard specimens, and their tensile strength (ASTM D638), flexural strength (ASTM D790), notched impact strength (ASTM D256), flame retardancy (UL94), and water absorption (ASTM D570) were tested respectively; and whether floating fibers appeared on the surface was observed. The specific properties are shown in Table 1-2.
[0073]
[0074]
[0075] It can be seen from the above table that the high-performance building composite material obtained by the invention has excellent mechanical properties, high impact strength, low water absorption and good surface smoothness.
[0076] It can be seen from Example 7 and Comparative Examples 1-5 that the addition of flat glass fiber and aramid fiber can greatly improve the mechanical properties and water absorption resistance of PA10T. Aramid fiber has excellent compatibility with PA10T, which can improve the dispersion performance of flat glass fiber in the PA10T matrix and prevent the occurrence of floating fiber phenomenon. The addition of aramid fiber not only plays a role in strengthening and toughening, but more importantly, it acts as a dispersing aid for flat glass fiber to improve the surface properties of the composite material and reduce the water absorption rate. If the amount of aramid fiber is too small, its reinforcement effect is limited; however, when the amount is too much, it is easy to cause uneven fiber dispersion and cause floating fiber phenomenon. Comparative Example 6 shows that PPO has high stiffness and low machinability. Excessive use of it may cause difficulties in the processing of the composite material, which is not conducive to the uniform dispersion of fiber fillers, reduces the mechanical properties and density of the composite material, and leads to a high water absorption rate.
[0077] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.
Claims
1. A high-performance composite material for construction, characterized in that: The composition comprises the following components in parts by weight: PA10T 80-90 parts, PPO 20-25 parts, flat glass fiber 20-30 parts, aramid fiber 5-10 parts, flame retardant 4-10 parts, coupling agent 1-5 parts, antioxidant 1-3 parts, flow modifier 1-3 parts; The PA10T melt index is 10-20 g / 10 min; The ratio of the major diameter to the minor diameter of the flat glass fiber is 2-10, and its length is 1-10 mm; The aramid fiber is Kevlar fiber, and its length is 1-10 mm.
2. A high-performance composite material for construction as claimed in claim 1, characterized in that: The flame retardant comprises a main flame retardant and a synergistic flame retardant; the main flame retardant is an alkyl phosphinate; the synergistic flame retardant is one or more of zinc borate, zinc oxide, aluminum oxide or magnesium hydroxide.
3. A high-performance composite material for construction as claimed in claim 1, characterized in that: The coupling agent is one or more of KH550, KH560 and KH570.
4. A high-performance composite material for construction as claimed in claim 1, characterized in that: The antioxidant is one or more of hindered phenol antioxidants, hindered amine antioxidants, phosphate antioxidants, and phosphite antioxidants.
5. A high-performance composite material for construction as claimed in claim 1, characterized in that: The flow modifier is one or more of silicone powder, polytetrafluoroethylene, amide wax, stearic acid amide, calcium stearate, and zinc stearate.
6. A method for preparing a high-performance composite material for construction as claimed in any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Place PA10T, PPO, flame retardant, coupling agent, antioxidant and flow modifier in a high-speed mixer and mix evenly; (2) The mixed material prepared in step (1) is added to an extruder through a main feed port, and flat glass fibers and aramid fibers are added to the extruder through a side feed port. The mixed material is melt-extruded, cooled, dried, and pelletized through the extruder to obtain a high-performance composite material for construction.
7. The method for preparing a high-performance composite material for construction according to claim 6, characterized in that: The heating temperature of the extruder is 310-330° C., and the screw speed is 500-700 r / min.
Citation Information
Patent Citations
Flame-retardant reinforced semi-aromatic nylon / polyphenylether composite and preparation method thereof
CN106609034A
High-performance low-wrapage nylon material as well as preparation method and application thereof
CN108192334A
Aramid fiber and glass fiber reinforced nylon 66 composite material and preparation method thereof
CN114907690A